Care of patients with autism spectrum disorder in a surgical ward, Chile - Lobos, Roberto (2020)
Objective: To describe nursing care in patients with autism spectrum disorder given by nurses who participate in the assistance activities of the surgical ward service in a private clinic. Material and methods: Quantitative descriptive study, the sample corresponded to 40 Nursing professionals who participate in health care within the surgical ward, who attend children between 1 and 15 years of age in a private clinic in the city of Iquique . For the nurses of the service, the Survey of Knowledge and Actions on the Care of Boys and Girls with ASD (ECA-ASD) was created, which allows describing sociodemographic characteristics, and assessing nursing care in a ward towards children. Results: It was appreciated that more than 90% of the professionals in this clinic do not have training regarding ASD, which reduces the performance of care appropriate to ASD. Conclusions: It is necessary to create a support system for the nursing professional in the care of ASD patients.